1979
DOI: 10.1099/00221287-112-2-397
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Atypical Lipopolysaccharides from Purified Cell Walls of Pseudomonas cepacia

Abstract: 397Wall fragments were prepared from two strains of Pseudomonas cepacia and from P. aeruginosa, and their contents of readily extractable lipid, pronase-digestible protein and lipopolysaccharide were measured. Lipopolysaccharide extracted from P. cepacia, although biologically active, contained no detectable 2-keto-3-deoxyoctonic acid, but contained phosphate, rhamnose, glucose, heptose and hexosamine in concentrations comparable to those found in P. aeruginosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…This idea is supported by the observation that P. cepacia was not permeabilized by EDTA (Table 1). Finally, it is possible that LPS from P. cepacia Mg2 (mM) the phosphate content of P. cepacia LPS was determined in one study (8) to be only one-third of that of P. aeruginosa LPS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This idea is supported by the observation that P. cepacia was not permeabilized by EDTA (Table 1). Finally, it is possible that LPS from P. cepacia Mg2 (mM) the phosphate content of P. cepacia LPS was determined in one study (8) to be only one-third of that of P. aeruginosa LPS.…”
Section: Resultsmentioning
confidence: 99%
“…The n value (Hill number) calculated from the Hill plots ( b Assuming LPS had a molecular weight of 9,000. For P. aeruginosa this was obtained by assuming that a measured weight of LPS contained two reactive 2-keto-3-deoxyoctonate molecules per LPS molecule (2,8). Since P. cepacia LPS had a similar pattern of distribution of LPS species on sodium dodecyl sulfate-polyacrylammide gel electrophoretograms as P. aeruginosa LPS (unpublished data), we assumed these LPS species had similar average molecular weights.…”
Section: Resultsmentioning
confidence: 99%
“…The part of the inner core region adjacent to the lipid A moiety in usual LPS is constructed of one to three molecules of 3-deoxy-D-mannooctulosonic acid (KDO) and is well conserved among various bacterial species. In the case of LPS extracted from B. cepacia, KDO was not detectable by the conventional method (17,33) but was detectable after hydrolyzing the LPS with strong acid (32). This suggests that the KDO portion of the inner core region in LPS of this organism is replaced by some molecules which provide acid resistance.…”
mentioning
confidence: 94%
“…Compared with LPS from P. aeruginosa that from strains of B. cepacia has less phosphorus and more heptose. Glucose and rhamnose were the major saccharide components of LPS from the organisms tested [42]. An extracellular material isolated from a clinical B. cepacia consisted of a surface carbohydrate antigen, LPS and protein, the toxicity of which appeared to be associated with the LPS portion of the complex [46].…”
Section: Extraceilular Virulence Factorsmentioning
confidence: 98%
“…Initial chemical analysis of B. cepacia LPS indicated the absence of detectable 3-deoxy-Dmanno-2-octulosonic acid (KDO) in LPS from B. cepacia [42,43]. However, Straus et al [44] reported the isolation of KDO from the culture supernate of 2 out of 10 strains of B. cepacia and in a further study KDO was demonstrated in 6 clinical isolates of B. cepacia and all 6 LPS preparations were equally toxic for mice when injected intraperitoneally [45].…”
Section: Extraceilular Virulence Factorsmentioning
confidence: 99%